Membrane material, preparation method and application thereof, and laminated glass
By using the first and second material layers with specific refractive index, melt index and dynamic viscosity difference in the diaphragm material, combined with the synergistic effect of plasticizer, the ghosting and mechanics of sound insulation PVB film in laminated glass is solved. The problem of degraded performance and aging resistance achieves higher sound insulation, mechanical and optical properties while reducing costs.
Patent Information
- Application Number
- CN202411561126.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-07
AI Technical Summary
Existing sound insulation PVB films are prone to problems such as ghosting, mechanical properties and aging resistance in laminated glass.
Using a diaphragm material composed of at least one first material layer and one second material layer, by adjusting the refractive index, melt index and dynamic viscosity difference of the material, the stability of the material under high temperature and high load conditions is ensured. And improve the fluidity and adhesion of the material through the synergistic action of plasticizers.
While maintaining good sound insulation performance, it can improve the mechanical properties, aging resistance and optical properties of the diaphragm materials, reduce production costs, and have significant economic benefits.
Smart Images

Figure CN119388858A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polymer materials, and in particular to a diaphragm material, a preparation method and application thereof, and laminated glass. Background Art
[0002] Polyvinyl Butyral (PVB for short) is a product of the condensation of polyvinyl alcohol and butyraldehyde under acid catalysis. Because PVB molecules contain relatively long side chains, they have good flexibility, low glass transition temperature, and high tensile strength and impact strength. PVB has excellent transparency, good solubility, and good light resistance, water resistance, heat resistance, cold resistance, and film-forming properties. The functional groups it contains can undergo various reactions such as saponification of acetyl groups, esterification of hydroxyl groups, and sulfonation, and react with glass and metals (especially aluminum). Therefore, it has been widely used in the manufacture of laminated safety glass, inks, adhesives, ceramic decals, aluminum foil, electrical materials, fiberglass products, fabric treatment agents, and other fields, becoming an indispensable synthetic resin material.
[0003] The front windshield of a car is usually composed of two layers of glass and a polyvinyl butyral film (PVB film for short). PVB film is used in the interlayer of the car windshield. When the glass collides and breaks, the PVB film firmly bonds the glass fragments, so that the broken glass always remains in one piece, thus preventing the broken glass from hurting people. Therefore, the use of PVB film in car windshields has become a mandatory requirement for safety glass. Because noise pollution affects the comfort of people's living and working environment, reducing noise is a very important indicator.
[0004] For soundproof PVB film, the performance of soundproof resin is a key factor affecting the performance of the film. Generally, soundproof PVB film achieves soundproof performance by using multi-layer composite technology, changing the structure of different layers of PVB resin or increasing the ratio of PVB plasticizer. However, PVB film with multi-layer composite technology is prone to ghosting problems in head-up display (HUD), which in turn affects driving safety; increasing the ratio of plasticizer to adjust the mechanical factors of different PVB film layers will cause problems such as decreased mechanical properties of the film and decreased aging resistance. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of ghosting, decreased mechanical properties and aging resistance when the sound insulation PVB film in the prior art is used for laminated glass, and to provide a diaphragm material and its preparation method and application, and laminated glass. The diaphragm material has good sound insulation performance and can improve its mechanical properties, aging resistance and optical properties, and has low cost and significant economic benefits.
[0006] In order to achieve the above-mentioned objectives, the first aspect of the present invention provides a diaphragm material, which includes at least one first material layer and at least one second material layer; the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melt index between the first material layer and the second material layer is not higher than 0.5g / 10min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400Pa·s.
[0007] Preferably, the refractive index of the first material layer is 1.47-1.49, the melt index under the conditions of a load of 21.6 kg and a temperature of 120° C. is 1.05-1.24, and the dynamic viscosity under the condition of a temperature of 180° C. is 1960-2180 Pa·s.
[0008] Preferably, the first material layer contains a first PVB resin and a first auxiliary agent, the second material layer contains a second PVB resin and a second auxiliary agent, the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, the second auxiliary agent contains a first plasticizer and a second plasticizer, and the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01.
[0009] Preferably, the first plasticizer is selected from at least one of triethylene glycol diisooctanoate, dioctyl azelate and dioctyl sebacate, and more preferably triethylene glycol diisooctanoate.
[0010] Preferably, the second plasticizer is at least one selected from dihexyl adipate, dioctyl phthalate, dioctyl terephthalate, dinonyl terephthalate and dioctyl adipate, and more preferably dioctyl adipate.
[0011] Preferably, the content of the first auxiliary agent in the first material layer is 26.0-28.5wt%.
[0012] Preferably, the hydroxyl value of the first PVB resin is 17-19 wt %.
[0013] Preferably, in the second material layer, the content of the second auxiliary agent is 42-46wt%.
[0014] Preferably, in the second material layer, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2.
[0015] Preferably, the hydroxyl value of the second PVB resin is 9-13 wt %.
[0016] Preferably, the membrane material includes two layers of the first material layer and one layer of the second material layer, and the two layers of the first material layer are arranged on both sides of the second material layer.
[0017] Preferably, the thickness of the first material layer is 280-320 μm, and the thickness of the second material layer is 80-120 μm.
[0018] Preferably, at least one side of the first material layer along the length direction is in a wedge-shaped structure from the middle to the end.
[0019] Preferably, the ratio of the maximum thickness of the first material layer to the thickness of the second material layer is 3.4-3.6:1.
[0020] A second aspect of the present invention provides a method for preparing a diaphragm material, comprising the following steps:
[0021] Extruding and pressing a first material to form a first material layer, extruding and pressing a second material to form a second material layer, and pressing at least one layer of the first material layer and at least one layer of the second material layer;
[0022] Among them, the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melt index between the first material layer and the second material layer is not higher than 0.5 g / 10 min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400 Pa·s.
[0023] Preferably, the preparation process of the first material includes: S1, mixing a first polyvinyl alcohol, a surfactant I, a catalyst I and butyraldehyde for heating reaction I to obtain a first PVB resin; S2, mixing the first PVB resin and a first auxiliary agent and then plasticizing and extruding; the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, and the weight ratio of the first auxiliary agent to the first PVB resin is 0.35-0.40:1.
[0024] Preferably, the preparation process of the second material includes: (a) mixing a second polyvinyl alcohol, a surfactant II, a catalyst II and butyraldehyde for heating reaction II to obtain a second PVB resin; (b) mixing the second PVB resin and a second auxiliary agent and then plasticizing and extruding; the second auxiliary agent contains a first plasticizer and a second plasticizer, and the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01. In the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2, and the weight ratio of the second auxiliary agent to the second PVB resin is 0.72-0.86:1.
[0025] Preferably, the first plasticizer is selected from at least one of triethylene glycol diisooctanoate, dioctyl azelate and dioctyl sebacate, and more preferably triethylene glycol diisooctanoate.
[0026] Preferably, the second plasticizer is at least one selected from dihexyl adipate, dioctyl phthalate, dioctyl terephthalate, dinonyl terephthalate and dioctyl adipate, and more preferably dioctyl adipate.
[0027] Preferably, the hydroxyl value of the first PVB resin is 17-19 wt %.
[0028] Preferably, the hydroxyl value of the second PVB resin is 9-13 wt %.
[0029] Preferably, the average polymerization degree of the first polyvinyl alcohol is 1600-1800.
[0030] Preferably, the first polyvinyl alcohol comprises polyvinyl alcohol I and polyvinyl alcohol II, the degree of polymerization of the polyvinyl alcohol I is 300-500, and the degree of polymerization of the polyvinyl alcohol II is 1800-2000.
[0031] Preferably, the average degree of polymerization of the second polyvinyl alcohol is 2400-2600.
[0032] Preferably, the second polyvinyl alcohol comprises polyvinyl alcohol III and polyvinyl alcohol IV, the degree of polymerization of the polyvinyl alcohol III is 1000-1500, and the degree of polymerization of the polyvinyl alcohol IV is 2600-2700.
[0033] Preferably, the surfactant I and the surfactant II are each independently selected from at least one of dioctyl sodium sulfosuccinate, dodecylbenzenesulfonic acid, sodium dodecyl sulfonate and sodium dodecyl sulfate.
[0034] Preferably, the catalyst I and the catalyst II are each independently selected from at least one of hydrochloric acid, sulfuric acid and maleic acid.
[0035] The third aspect of the present invention provides the use of the membrane material described in the first aspect and / or the membrane material obtained by the preparation method described in the second aspect in laminated glass.
[0036] A fourth aspect of the present invention provides a laminated glass, comprising the membrane material described in the first aspect and / or the membrane material obtained by the preparation method described in the second aspect and two glass layers, wherein the membrane material is located between the two glass layers.
[0037] Through the above technical scheme, the diaphragm material provided by the present invention includes at least one first material layer and at least one second material layer, and the first material layer and the second material layer have a specific refractive index difference, melt index difference and viscosity difference. The first material layer and the second material layer are superimposed to form a synergistic effect, so that the diaphragm material has good sound insulation performance while improving its weather resistance and adhesion to laminated glass, and improves the optical ghosting imaging problem generated when the first material layer and the second material layer are superimposed, thereby improving its optical performance, while reducing production costs, and having significant economic benefits. The preparation process of the diaphragm material is easy to operate and is very suitable for industrial production. When it is applied to laminated glass, the sound insulation and long-term bonding stability of laminated glass can be improved.
[0038] Furthermore, the second material layer, through the synergistic effect of the first plasticizer and the second plasticizer, can improve the solubility of the two plasticizers in the second PVB resin while ensuring the sound insulation performance of the diaphragm material, thereby improving the fluidity of the second material layer and the adhesion of the diaphragm material, while greatly reducing the cost of the second material layer, and can further improve the optical ghosting imaging problem caused by the superposition of the first material layer and the second material layer; by controlling the hydroxyl value of the first PVB resin and the second PVB resin within a specific range, the weather resistance of the diaphragm material can be significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a schematic diagram of the first structure of the ABA distributor mold with a planar structure for preparing the membrane material in the present invention;
[0040] Figure 2 This is a second structural schematic diagram of the ABA distributor mold with a planar structure for preparing the membrane material in the present invention;
[0041] Figure 3 This is a schematic diagram of the first structure of the ABA distributor mold with a wedge-shaped structure for preparing the diaphragm material in the present invention;
[0042] Figure 4 This is a second structural schematic diagram of the ABA distributor mold with a wedge-shaped structure for preparing the diaphragm material in the present invention;
[0043] Figure 5 It is a third structural schematic diagram of the ABA distributor mold with a wedge-shaped structure for preparing the diaphragm material in the present invention. DETAILED DESCRIPTION
[0044] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0045] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0046] In the first aspect, the present invention provides a diaphragm material, which includes at least one first material layer and at least one second material layer; the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melt index between the first material layer and the second material layer is not higher than 0.5g / 10min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400Pa·s.
[0047] During the research process, the inventors of the present invention discovered that the synergistic effect formed by the superposition of the first material layer and the second material layer due to the specific refractive index difference, melt index difference and dynamic viscosity difference allows the diaphragm material to have better sound insulation performance while improving its weather resistance and adhesion to the laminated glass, thereby improving the optical image produced when the first material layer and the second material layer are superimposed, thereby improving its optical performance, and effectively reducing production costs, thereby having significant economic benefits.
[0048] In the present invention, the difference in refractive index between the first material layer and the second material layer is not higher than 0.01, which means that the absolute value of the difference obtained by subtracting the refractive index of the first material layer from the refractive index of the second material layer is not higher than 0.01. The refractive index of the first material layer may be greater than the refractive index of the second material layer, or may be less than the refractive index of the second material layer; similarly, the difference in melt index and dynamic viscosity between the first material layer and the second material layer refers to the absolute values of the corresponding differences.
[0049] In the present invention, the refractive indexes of the first material layer and the second material layer are measured by using an Abbe refractometer, and the test wavelength is set to 589 nm.
[0050] In the present invention, the melt index of the first material layer and the second material layer is obtained by testing with a melt index meter (model: XNR-400E). The specific testing process includes: (1) before using the instrument, adjust the level; turn on the power, set the temperature to 120°C, heat, and when the temperature displayed by the digital thermometer reaches 120°C, keep the temperature constant for 20-30 minutes. Set the parameters: the sampling mode is "time control", the sampling time is 300s, and the load is 21.6kg; (2) Use an electronic balance to weigh 1.250±0.001g of plasticizer and 3.750±0.001g of the sample to be tested, respectively, stir with a glass rod to mix evenly, take out the guide sleeve and the plunger, quickly add the mixture into the barrel with a funnel, add the plunger and the guide sleeve, put the weight on and press it tightly, and the whole process is required to be completed within one minute; preheat for 4 minutes, press the test button to test, take six sections of material continuously, cool and weigh, and the obtained weight is converted into the melt index; (3) After the measurement is completed, remove the weight, take out the guide sleeve and the plunger, use the cleaning rod to gently press the die out of the barrel, and immediately use the die drill to clean the inner hole, and then wipe the outer surface with cotton gauze, wrap the cotton gauze around the head of the cleaning rod, insert it into the barrel and wipe until the barrel is clean.
[0051] In the present invention, the dynamic viscosity of the first material layer and the second material layer is measured by a precision rheometer (model RosandRH7), and the parameter settings include: temperature of 180°C, shear stress of 40±0.1kPa, load force of 0.5±0.01kN, shear rate of 20±0.2s -1 , pressure is 2.5±0.1MPa, and measuring speed is 0.65±0.05mm / min.
[0052] According to the present invention, in order to enable the diaphragm material to have better sound insulation performance while further improving its weather resistance, adhesion between laminated glass and optical properties, preferably, the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melting index between the first material layer and the second material layer is not higher than 0.2g / 10min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 200Pa·s.
[0053] According to the present invention, preferably, the refractive index of the first material layer is 1.47-1.49, the melt index under the conditions of a load of 21.6 kg and a temperature of 120° C. is 1.05-1.24, and the dynamic viscosity under the condition of a temperature of 180° C. is 1960-2180 Pa·s. The inventors have found that under this preferred embodiment, the first material layer having a specific refractive index, melt index and dynamic viscosity has good bonding properties.
[0054] In the present invention, the film material contains polyvinyl acetal resin, and preferably, the polyvinyl acetal resin is polyvinyl butyral (PVB) resin.
[0055] According to the present invention, preferably, the first material layer contains a first PVB resin and a first auxiliary agent, the second material layer contains a second PVB resin and a second auxiliary agent, the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, the second auxiliary agent contains a first plasticizer and a second plasticizer, and the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01. The inventors found that under this preferred embodiment, the first PVB resin and the first plasticizer have good compatibility, and the first material layer can improve the bonding performance of the first material layer through the cooperation of the first PVB resin and the first plasticizer, thereby improving the adhesion of the diaphragm material; the second PVB resin, the first plasticizer and the second plasticizer have good compatibility, and the second material layer can improve the fluidity of the second material layer and reduce the cost of the second material layer while ensuring the sound insulation performance of the diaphragm material through the cooperation of the second PVB resin, the first plasticizer and the second plasticizer, and can also improve the optical image produced when the first material layer and the second material layer are superimposed, further improving the driving safety of the vehicle.
[0056] According to the present invention, in order to further improve the fluidity and adhesion of the diaphragm material, preferably, the first plasticizer is selected from at least one of triethylene glycol diisooctanoate (CAS No. 94-28-0, abbreviated as 3GO), dioctyl azelaic acid (CAS No. 26544-17-2) and dioctyl sebacate (CAS No. 2432-87-3), and triethylene glycol diisooctanoate is further preferred.
[0057] According to the present invention, in order to further improve the fluidity and adhesion of the diaphragm material, preferably, the second plasticizer is selected from at least one of dihexyl adipate (CAS No. 110-33-8, referred to as DHA), dioctyl phthalate (CAS No. 117-84-0, referred to as DOP), dioctyl terephthalate (CAS No. 6422-86-2, referred to as DOTP), dinonyl terephthalate (CAS No. 4654-27-7) and dioctyl adipate (CAS No. 123-79-5, referred to as DOA), and dioctyl adipate is further preferably selected.
[0058] In the present invention, the first auxiliary agent may contain antioxidant I and ultraviolet light absorber I in addition to the first plasticizer; the second auxiliary agent may contain antioxidant II and ultraviolet light absorber II in addition to the first plasticizer and the second plasticizer. Antioxidant I and antioxidant II may be the same or different; ultraviolet light absorber I and ultraviolet light absorber II may be the same or different. The inventors have found that under this preferred embodiment, the weather resistance of the diaphragm material can be further improved. There is no particular limitation on the type and content of antioxidant I and ultraviolet light absorber I in the first auxiliary agent, and they can be conventional choices in the art; there is no particular limitation on the type and content of antioxidant II and ultraviolet light absorber II in the second auxiliary agent, and they can be conventional choices in the art.
[0059] According to the present invention, in order to further improve the bonding performance of the first material layer and the adhesion of the film material, preferably, the content of the first auxiliary agent in the first material layer is 26.0-28.5wt%, specifically 26.0wt%, 27.0wt%, 28.5wt%, or any value between the above two values. The inventors found that under this preferred embodiment, the higher the content of the first auxiliary agent, the better the bonding performance of the first material layer.
[0060] According to the present invention, preferably, the hydroxyl value of the first PVB resin is 17-19wt%, specifically 17wt%, 18wt%, 19wt%, or any value between the above two values. The inventors found that under this preferred embodiment, the weather resistance of the film material is further improved; moreover, the greater the hydroxyl value of the first PVB resin, the better the weather resistance of the film material, and the better the lamination performance with glass.
[0061] According to the present invention, in order to further improve the weather resistance of the film material, preferably, in the second material layer, the total content of the second auxiliary agent is 42-46wt%, specifically 42wt%, 44wt%, 46wt%, or any value between the above two values. The higher the total content of the second auxiliary agent, the better the optical properties of the film material.
[0062] According to the present invention, in order to further improve the optical properties of the diaphragm material and reduce the cost of the second material layer, preferably, in the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2, specifically 1:0.8, 1:1, 1:1.2, or any value between the two aforementioned values. The inventors have found that under this preferred embodiment, through the synergistic effect of the first plasticizer and the second plasticizer in a specific dosage ratio, the fluidity of the second material layer and the adhesion of the diaphragm material can be improved while ensuring the sound insulation performance of the diaphragm material, thereby reducing the cost of the second material layer and further improving the optical image produced when the first material layer and the second material layer are superimposed; moreover, the greater the weight ratio of the first plasticizer to the second plasticizer, the better the adhesion and optical properties of the diaphragm material.
[0063] According to the present invention, preferably, the hydroxyl value of the second PVB resin is 9-13wt%, specifically 9wt%, 11wt%, 13wt%, or any value between the above two values. The inventors found that under this preferred embodiment, the weather resistance of the membrane material and its lamination performance with glass are further improved; moreover, the greater the hydroxyl value of the second PVB resin, the better the weather resistance of the membrane material and the better the lamination performance with glass.
[0064] In the present invention, the hydroxyl values of the first PVB resin and the second PVB resin are obtained by measuring the mass percentage of the hydroxyl group of the polyvinyl acetal resin by the acetic acid method. The specific testing process includes:
[0065] (1) Test steps: accurately weigh 1 g (accurate value is 0.1 mg) of polyvinyl acetal sample and put it into a 250 ml ground-mouth conical flask; prepare 90 ml of pyridine and 10 ml of acetic anhydride in a fume hood and mix them in the conical flask; use a pipette to add 10 ml of the mixture of pyridine and acetic anhydride to the polyvinyl acetal sample; install a condenser in the conical flask, heat it to 95°C and reflux it until the sample is completely dissolved, about 3 hours; cool the mixture to room temperature, and then add 25 ml of 1,2-dichloroethane from the top of the condenser; remove the condenser, cover it with a stopper, and shake it gently; add 5 ml of distilled water to wash the stopper and the bottle wall, shake it gently, and leave it for 1 hour; use a pipette to transfer 25 ml of distilled water to rinse along the wall of the conical flask; add 2 ml of phenolphthalein indicator; titrate with 0.5 mol / L sodium hydroxide standard solution;
[0066] (2) Expression of analysis results: The reaction product acetic acid can be detected by 0.5 mol / L sodium hydroxide standard solution. Let V s represents the volume of neutralized acetic acid NaOH, and the mass of the neutralized sample is E; let V bIt indicates the volume of NaOH standard solution consumed by the blank sample, that is, the volume of acetic acid completely converted from acetic anhydride in the blank sample. 1 mol of acetic acid corresponds to 1 mol of polyvinyl alcohol (44 g);
[0067] The hydroxyl content is calculated according to formula (I):
[0068]
[0069] In formula (I), X is the hydroxyl content, expressed in percentage (%); V b V is the volume of sodium hydroxide standard solution consumed in titrating the blank sample, in milliliters (ml); s is the volume of sodium hydroxide standard solution consumed in titrating the sample, in milliliters (ml); C is the actual concentration of the sodium hydroxide standard solution, in moles per liter (mol / L); E is the mass of the sample, in grams (g); H is the volatile content of the sample, in percentage (%);
[0070] (3) Two parallel tests should be performed and their arithmetic mean should be taken as the test result. The valid value should be rounded to two decimal places in accordance with the provisions of "GB / T 8170-2008 Numerical Rounding Rules and Representation and Determination of Limit Values"; the difference between the two values of the parallel test results shall not exceed 0.3%.
[0071] According to the present invention, the diaphragm material may include a first material layer and a second material layer, may include a first material layer and two second material layers, or may include two first material layers and a second material layer. In order to further improve the weather resistance, lamination performance and optical performance of the diaphragm material while ensuring the sound insulation performance of the diaphragm material, preferably, the diaphragm material includes two first material layers and one second material layer, the two first material layers are arranged on both sides of the second material layer, and more preferably, the two first material layers are symmetrically arranged on both sides of the second material layer.
[0072] According to the present invention, in order to further improve the weather resistance, lamination performance and optical properties of the membrane material, preferably, the thickness of the first material layer is 280-320μm, specifically 280μm, 300μm, 320μm, or any value between the aforementioned two values; the thickness of the second material layer is 80-120μm, specifically 80μm, 100μm, 120μm, or any value between the aforementioned two values.
[0073] In the present invention, in the membrane material, the first material layer and the second material layer may have the same thickness; or one of them may have the same thickness and the other may have a different thickness. It should be noted that the first material layer and the second material layer having the same thickness means that the thickness at any position along the length direction of the first material layer or the second material layer is the same.
[0074] For example, Figure 1 It is an ABA dispenser mold with a planar structure. In the diaphragm material prepared by the mold, A is the first material layer, B is the second material layer, and the first material layer and the second material layer have the same thickness. Figure 2 For an ABA dispenser mold with external baffles, the external baffles C and D can be used to adjust the width of the sound insulation lamination.
[0075] For example, Figure 3 , Figure 4 and Figure 5 It is an ABA distributor mold with a wedge-shaped structure. In the diaphragm material prepared by the mold, A is the first material layer, B is the second material layer, the second material layers have the same thickness, and the m segments of the first material layer gradually decrease in thickness from left to right.
[0076] According to the present invention, preferably, at least one side of the first material layer along the length direction is in a wedge-shaped structure from the middle to the end. The inventors have found that the wedge-shaped structure reduces the ghosting phenomenon of two parallel glass sheets when applied to laminated glass, while achieving the effect of a head-up display.
[0077] According to the present invention, at least one side of the first material layer along the length direction is wedge-shaped from the middle to the end, see Figure 3 , wherein the wedge-shaped structure from the middle to the end means that the thickness of the m segments on one side of the first material layer gradually decreases from left to right. The first material layer may have a wedge-shaped structure on one side along the length direction, or the first material layer may have a wedge-shaped structure on both sides along the length direction.
[0078] In the present invention, the Figure 4-Figure 5 In the diaphragm material prepared by the ABA distributor mold with a wedge-shaped structure shown, A is the first material layer, B is the second material layer, when the N segments on both sides of the first material layer along the length direction are wedge-shaped structures, M segments are arranged between the N segments on both sides, and the M segments have the same thickness, when the diaphragm material is used for laminated glass, the ghosting phenomenon of two parallel glass sheets can be further reduced.
[0079] According to the present invention, in order to further improve the sound insulation and optical properties of the diaphragm material, preferably, the ratio of the maximum thickness of the first material layer to the thickness of the second material layer is 3.4-3.6:1, specifically 3.4:1, 3.5:1, 3.6:1, or any value between the above two values.
[0080] In a second aspect, the present invention provides a method for preparing a membrane material, comprising the following steps:
[0081] The first material is extruded and pressed to form a first material layer, the second material is extruded and pressed to form a second material layer, and at least one layer of the first material layer and at least one layer of the second material layer are pressed; wherein the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120° C., the difference in melt index between the first material layer and the second material layer is not higher than 0.5 g / 10 min; under the condition of a temperature of 180° C., the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400 Pa·s.
[0082] According to the present invention, the preparation method of the diaphragm material is simple and suitable for industrial production.
[0083] In the present invention, the method for obtaining the diaphragm material by pressing the first material and the second material can adopt a method conventionally selected in the art. For example, the first material and the second material can be extruded and pressed to form a first material layer and a second material layer, and then the first material layer and the second material layer are pressed to obtain the diaphragm material; the first material and the second material can also be co-extruded to obtain the first material layer and the second material layer pressed together. Preferably, the first material and the second material are co-extruded to obtain the first material layer and the second material layer pressed together.
[0084] According to the present invention, preferably, the co-extrusion molding temperature is 160-180°C, specifically 160°C, 170°C, 180°C, or any value between the aforementioned two values.
[0085] According to the present invention, preferably, the preparation process of the first material includes: S1, mixing a first polyvinyl alcohol, a surfactant I, a catalyst I and butyraldehyde for heating reaction I to obtain a first PVB resin; S2, mixing the first PVB resin and a first auxiliary agent and plasticizing and extruding; the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, and the weight ratio of the first auxiliary agent to the first PVB resin is 0.35-0.40:1, specifically 0.35:1, 0.37:1, 0.40:1, or any value between the above two values. The inventors found that under this preferred embodiment, the first material layer improves the adhesion of the first material layer through the coordination of the first PVB resin and the first auxiliary agent in a specific dosage ratio, thereby improving the lamination performance of the membrane material.
[0086] According to the present invention, preferably, the preparation process of the second material includes: (a) mixing a second polyvinyl alcohol, a surfactant II, a catalyst II and butyraldehyde for heating reaction II to obtain a second PVB resin; (b) mixing the second PVB resin and a second auxiliary agent and plasticizing and extruding; the second auxiliary agent contains a first plasticizer and a second plasticizer, the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01, and in the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2, specifically 1:0.8, 1:1, 1:1.2, or any value between the above two values; the weight ratio of the second auxiliary agent to the second PVB resin is 0.72-0.86:1, specifically 0.72:1, 0.8:1, 0.86:1, or any value between the above two values. The inventors have discovered that under this preferred embodiment, the second material layer, through the coordinated effect of the second PVB resin and the second auxiliary agent in a specific dosage ratio, and combined with the synergistic effect of the first plasticizer and the second plasticizer in a specific dosage ratio, can ensure the sound insulation performance of the diaphragm material while improving the solubility of the first plasticizer and the second plasticizer in the second auxiliary agent in the second PVB resin, thereby improving the fluidity of the second material layer and reducing the cost of the second material layer. Moreover, it can improve the optical image produced when the first material layer and the second material layer are superimposed, thereby improving the driving safety of the vehicle.
[0087] According to the present invention, in order to further improve the fluidity and adhesion of the membrane material, preferably, the first plasticizer is selected from at least one of triethylene glycol diisooctanoate, dioctyl azelate and dioctyl sebacate, and more preferably triethylene glycol diisooctanoate.
[0088] According to the present invention, in order to further improve the fluidity and adhesion of the membrane material, preferably, the second plasticizer is selected from at least one of dihexyl adipate, dioctyl phthalate, dioctyl terephthalate, dinonyl terephthalate and dioctyl adipate, and more preferably dioctyl adipate.
[0089] In the present invention, the first auxiliary agent may contain antioxidant I and ultraviolet light absorber I in addition to the first plasticizer; the second auxiliary agent may contain antioxidant II and ultraviolet light absorber II in addition to the first plasticizer and the second plasticizer. Antioxidant I and antioxidant II may be the same or different; ultraviolet light absorber I and ultraviolet light absorber II may be the same or different. The inventors have found that under this preferred embodiment, the weather resistance of the film material can be further improved.
[0090] In the present invention, there is no particular limitation on the type and content of antioxidant I and ultraviolet light absorber I in the first auxiliary agent, and they can be conventionally selected in the art; there is no particular limitation on the type and content of antioxidant II and ultraviolet light absorber II in the second auxiliary agent, and they can be conventionally selected in the art. In order to further improve the weather resistance of the membrane material, preferably, antioxidant I and antioxidant II are selected from at least one of octylphenol, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, 2,2'-methylenebis(4-methyl-6-tert-butylphenol) and β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate; ultraviolet light absorber I and ultraviolet light absorber II are each independently a benzotriazole ultraviolet light absorber.
[0091] According to the present invention, in order to further improve the weather resistance and lamination performance of the film material, preferably, the hydroxyl value of the first PVB resin is 17-19wt%, specifically 17wt%, 18wt%, 19wt%, or any value between the above two values.
[0092] According to the present invention, in order to further improve the weather resistance and lamination performance of the film material, preferably, the hydroxyl value of the second PVB resin is 9-13wt%, specifically 9wt%, 11wt%, 13wt%, or any value between the above two values.
[0093] According to the present invention, preferably, the average degree of polymerization of the first polyvinyl alcohol is 1600-1800. The inventors found that under this preferred embodiment, the adhesion of the first material layer during the lamination process can be improved.
[0094] According to the present invention, preferably, the first polyvinyl alcohol comprises polyvinyl alcohol I and polyvinyl alcohol II, the degree of polymerization of the polyvinyl alcohol I is 300-500; the degree of polymerization of the polyvinyl alcohol II is 1800-2000. The inventors found that under this preferred embodiment, the adhesion of the first material layer during the lamination process can be further improved through the synergistic effect of polyvinyl alcohol I and polyvinyl alcohol II within a specific degree of polymerization range.
[0095] According to the present invention, preferably, the average degree of polymerization of the second polyvinyl alcohol is 2400-2600. The inventors found that under this preferred embodiment, the adhesion of the second material layer during the lamination process can be improved.
[0096] According to the present invention, preferably, the second polyvinyl alcohol comprises polyvinyl alcohol III and polyvinyl alcohol IV, the degree of polymerization of the polyvinyl alcohol III is 1000-1500; the degree of polymerization of the polyvinyl alcohol IV is 2600-2700. The inventors found that under this preferred embodiment, the adhesion of the second material layer during the lamination process can be further improved through the synergistic effect of polyvinyl alcohol III and polyvinyl alcohol IV within a specific degree of polymerization range.
[0097] In the present invention, the alcoholysis degree of polyvinyl alcohol I, polyvinyl alcohol II, polyvinyl alcohol III and polyvinyl alcohol IV is independently above 90%, which can be adjusted according to the requirements of the prepared PVB. Preferably, the alcoholysis degree of polyvinyl alcohol I, polyvinyl alcohol II, polyvinyl alcohol III and polyvinyl alcohol IV is independently 98.2-99.5%.
[0098] According to the present invention, in order to further improve the reaction efficiency and yield of the first material or the second material, preferably, the surfactant I and the surfactant II are each independently selected from at least one of dioctyl sodium sulfosuccinate, dodecylbenzenesulfonic acid, sodium dodecyl sulfonate and sodium dodecyl sulfate, and dioctyl sodium sulfosuccinate is further preferred.
[0099] According to the present invention, catalyst I and catalyst II can be acid catalysts. In order to further improve the reaction efficiency and yield of the first material or the second material, preferably, the catalyst I and the catalyst II are each independently selected from at least one of hydrochloric acid, sulfuric acid and maleic acid, more preferably hydrochloric acid, and further preferably a hydrochloric acid aqueous solution with a hydrochloric acid concentration of 30-35wt%.
[0100] According to the present invention, in step S1, the conditions for heating reaction I at least include: a temperature of 65-70°C, specifically 65°C, 68°C, 70°C, or any value between the foregoing two values.
[0101] According to the present invention, in step S1, the process of mixing the first polyvinyl alcohol, the surfactant I, the catalyst I and the butyraldehyde comprises: dissolving the first polyvinyl alcohol in water at 98-100°C, cooling to 15-30°C, adding the surfactant I, the catalyst I and the butyraldehyde to the solution for heating reaction I, washing the suspension obtained after the heating reaction I with water, adjusting its pH to 10.5-11, separating and drying to obtain the first PVB resin. The inventors found that under this preferred embodiment, dissolving the first polyvinyl alcohol in water first is conducive to reacting with butyraldehyde, and the product is evenly dispersed.
[0102] According to the present invention, in step S1, there is no particular limitation on the amount of the first polyvinyl alcohol, surfactant I, catalyst I and butyraldehyde. In order to further improve the efficiency of the reaction, preferably, the amount ratio of the first polyvinyl alcohol, surfactant I, catalyst I and butyraldehyde is 1:0.002-0.005:0.1-0.2:0.5-1.
[0103] According to the present invention, in step (a), the conditions for heating reaction II at least include: a temperature of 65-70°C, specifically 65°C, 68°C, 70°C, or any value between the foregoing two values.
[0104] According to the present invention, in step (a), the process of mixing the second polyvinyl alcohol, surfactant II, catalyst II and butyraldehyde comprises: dissolving the second polyvinyl alcohol in water at 98-100°C, cooling to 15-30°C, adding surfactant II, catalyst II and butyraldehyde to the solution for heating reaction II, washing the suspension obtained after heating reaction II with water, adjusting its pH to 10.5-11, separating and drying to obtain the second PVB resin. The inventors found that under this preferred embodiment, dissolving the second polyvinyl alcohol in water first is conducive to reacting with butyraldehyde, and the product is evenly dispersed.
[0105] According to the present invention, in step (a), there is no particular limitation on the amount of the second polyvinyl alcohol, surfactant II, catalyst II and butyraldehyde. In order to further improve the efficiency of the reaction, preferably, the amount ratio of the second polyvinyl alcohol, surfactant II, catalyst II and butyraldehyde is 1:0.002-0.005:0.1-0.2:0.9-1.1.
[0106] According to a particularly preferred embodiment of the present invention, the method for preparing the diaphragm material comprises the following steps:
[0107] The first material and the second material are compounded together by co-extrusion molding, and the co-extrusion molding temperature is 160-180° C.; wherein the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120° C., the difference in melt index between the first material layer and the second material layer is not higher than 0.5 g / 10 min; under the condition of a temperature of 180° C., the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400 Pa·s;
[0108] The preparation process of the first material includes: S1, mixing a first polyvinyl alcohol, a surfactant I, a catalyst I and butyraldehyde, and heating and reacting them to obtain a first PVB resin; S2, mixing the first PVB resin and a first auxiliary agent, and then plasticizing and extruding; the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, and the weight ratio of the first auxiliary agent to the first PVB resin is 0.35-0.40:1;
[0109] The preparation process of the second material includes: (a) mixing a second polyvinyl alcohol, a surfactant II, a catalyst II and butyraldehyde to perform a heating reaction II to obtain a second PVB resin; (b) mixing the second PVB resin and a second auxiliary agent and then plasticizing and extruding; the second auxiliary agent contains a first plasticizer and a second plasticizer, the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01, and in the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2, and the weight ratio of the second auxiliary agent to the second PVB resin is 0.72-0.86:1;
[0110] The first plasticizer is triethylene glycol diisooctanoate; the second plasticizer is dioctyl adipate; the hydroxyl value of the first PVB resin is 17-19wt%; the hydroxyl value of the second PVB resin is 9-13wt%; the average degree of polymerization of the first polyvinyl alcohol is 1600-1800; the first polyvinyl alcohol includes polyvinyl alcohol I and polyvinyl alcohol II, the degree of polymerization of polyvinyl alcohol I is 300-500, and the degree of polymerization of polyvinyl alcohol II is 1800-2000; the average degree of polymerization of the second polyvinyl alcohol is 2400-2600; the second polyvinyl alcohol includes polyvinyl alcohol III and polyvinyl alcohol IV, the degree of polymerization of polyvinyl alcohol III is 1000-1500, and the degree of polymerization of polyvinyl alcohol IV is 2600-2700; the surfactant I and the surfactant II are each independently selected from at least one of dioctyl sodium sulfosuccinate, dodecylbenzene sulfonic acid, sodium dodecyl sulfonate and sodium dodecyl sulfate; the catalyst I and the catalyst II are each independently selected from at least one of hydrochloric acid, sulfuric acid and maleic acid.
[0111] The diaphragm material prepared by the above particularly preferred embodiment has good sound insulation performance, and at the same time can improve its weather resistance and adhesion with laminated glass, and improve the optical performance.
[0112] In a third aspect, the present invention provides use of the membrane material described in the first aspect and / or the membrane material obtained by the preparation method described in the second aspect in laminated glass.
[0113] In a fourth aspect, the present invention provides a laminated glass comprising the membrane material described in the first aspect and / or the membrane material obtained by the preparation method described in the second aspect and two glass layers, wherein the membrane material is located between the two glass layers.
[0114] It should be noted that, in addition to the two glass layers, the laminated glass may also be provided with other glass layers, and the membrane material provided by the present invention may be provided between the other adjacent glass layers, or may not be provided with the membrane material.
[0115] The present invention will be described in detail below through examples. In the following examples, triethylene glycol diisooctanoate (3GO) was purchased from Lanxi Wanshengda Chemical Co., Ltd., and the model was triethylene glycol diisooctanoate plasticizer; dioctyl adipate (DOA) was purchased from Huangshan Hanghua Chemical Technology Co., Ltd.; polyvinyl alcohol with a degree of polymerization of 300, 500, 1000, 1700, 1800, 2500, and 2700 was self-produced, and the models were 0399, 05-99, 10-99, 1798, 1798, 24-99, and 26-99, respectively; ultraviolet light absorber Tinuvin@P was purchased from Guangzhou Yinuo Chemical Technology Co., Ltd., and the model was Chimassorb 81; ultraviolet light absorber Tinuvin@571 was purchased from Chengdu Jingyi New Materials Co., Ltd., and the model was UV-571; octylphenol antioxidant was purchased from Shanghai Minke New Materials Co., Ltd., and the model was OP-30; unless otherwise specified, the remaining raw materials or reagents were conventional commercially available products.
[0116] Example 1
[0117] (1) polyvinyl alcohol with a degree of polymerization of 300 and polyvinyl alcohol with a degree of polymerization of 1800 are mixed in a weight ratio of 6:94 to obtain a polyvinyl alcohol mixture with an average degree of polymerization of 1700, 35 parts by weight of the polyvinyl alcohol mixture are dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water is 1:9) to obtain a polyvinyl alcohol solution, which is then cooled to 20° C.; then 0.14 parts by weight of sodium dioctyl sulfosuccinate, 5 parts by weight of hydrochloric acid (concentration 30-35wt%) and 20.5 parts by weight of ethanol are added to the polyvinyl alcohol solution. n-butyraldehyde, reacting at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 18.5 wt% is obtained; washing the polyvinyl butyral suspension with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1 wt%; raising the pH value of the mixture to 11 with a sodium hydroxide solution to stabilize it; subsequently, removing water with a centrifugal dryer, and air drying the mixture in an airflow drying device to a moisture content of ≤1 wt%, to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 18.5 wt%;
[0118] (2) A 3GO plasticizer containing Tinuvin@P, Tinuvin@571 and an octylphenol antioxidant (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, and the amount of octylphenol antioxidant is 8g) is used as a first auxiliary agent, and the pellets obtained in step (1) and the first auxiliary agent are mixed in a twin-screw extruder to obtain a first material; wherein the feed weight rate ratio of the first auxiliary agent to the pellets is 28:72, and an aqueous solution with a molar ratio of potassium acetate to magnesium acetate of 3:1 is injected during extrusion (the amount of the aqueous solution is 0.02% by weight of the plasticizer);
[0119] (3) polyvinyl alcohol with a degree of polymerization of 1000 and polyvinyl alcohol with a degree of polymerization of 2700 were mixed in a weight ratio of 10:90 to obtain a polyvinyl alcohol mixture with an average degree of polymerization of 2500, 35 parts by weight of the polyvinyl alcohol mixture were dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water was 1:9) to obtain a polyvinyl alcohol solution, which was cooled to 20° C.; then 0.14 parts by weight of sodium dioctyl sulfosuccinate, 5 parts by weight of hydrochloric acid (concentration 30-35wt%) and 35.7 parts by weight of sodium succinate were added to the polyvinyl alcohol solution; parts of n-butyraldehyde, reacting at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 11.5wt% is obtained; the polyvinyl butyral suspension is washed with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1wt%; the pH value of the mixture is increased to 11 with a sodium hydroxide solution to stabilize it; subsequently, a centrifugal dryer is used to remove water, and the mixture is air-dried in an airflow drying device to have a water content of ≤1wt%, to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 11.5wt%;
[0120] (4) using 3GO plasticizer and DOA plasticizer containing Tinuvin@P, Tinuvin@571 and octylphenol antioxidant (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, the amount of octylphenol antioxidant is 8g, and the amount ratio of 3GO plasticizer to DOA plasticizer is 50:50) as the second auxiliary agent, and mixing the pellets obtained in step (3) with the second auxiliary agent in a twin-screw extruder to obtain a second material; wherein the feed weight rate ratio of the second auxiliary agent to the pellets is 45:55;
[0121] (5) The first material and the second material are passed through an ABA distributor, wherein A is the first material, B is the second material, and the thickness ratio of A to B is 3.4:1, to obtain a membrane material; the ABA distributor used is Figure 1 The mold shown.
[0122] Example 2
[0123] (1) polyvinyl alcohol having a degree of polymerization of 500 and polyvinyl alcohol having a degree of polymerization of 1800 are mixed in a weight ratio of 8:92 to obtain a polyvinyl alcohol mixture having an average degree of polymerization of 1700; 35 parts by weight of the polyvinyl alcohol mixture are dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water is 1:9) to obtain a polyvinyl alcohol solution, which is then cooled to 20° C.; then 0.07 parts by weight of sodium dioctyl sulfosuccinate, 7 parts by weight of hydrochloric acid and 35 parts by weight of n-butyraldehyde are added to the polyvinyl alcohol solution; and the mixture is stirred at 65° C. for 24 hours. The reaction was carried out at -70°C until a polyvinyl butyral suspension having a hydroxyl content of 18.5 wt% was obtained; the polyvinyl butyral suspension was washed with deionized water for 20 minutes each time until the residual butyraldehyde content was ≤1 wt%; the pH value of the mixture was increased to 11 with a sodium hydroxide solution to stabilize it; subsequently, a centrifugal dryer was used to remove water, and the mixture was air-dried in an airflow drying device to have a water content of ≤1 wt%, to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 18.5 wt%;
[0124] (2) A 3GO plasticizer containing Tinuvin@P, Tinuvin@571 and an octylphenol antioxidant (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, and the amount of octylphenol antioxidant is 8g) is used as a first auxiliary agent, and the pellets obtained in step (1) and the first auxiliary agent are mixed in a twin-screw extruder to obtain a first material; wherein the feed weight rate ratio of the first auxiliary agent to the pellets is 28:72, and an aqueous solution with a molar ratio of potassium acetate to magnesium acetate of 3:1 is injected during extrusion (the amount of the aqueous solution is 0.05% by weight of the plasticizer), and the melting temperature measured by sampling at the end of the extruder is between 170°C and 185°C;
[0125] (3) polyvinyl alcohol with a degree of polymerization of 1000 and polyvinyl alcohol with a degree of polymerization of 2700 were mixed in a weight ratio of 10:90 to obtain a polyvinyl alcohol mixture with an average degree of polymerization of 2500, 35 parts by weight of the polyvinyl alcohol mixture were dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water was 1:9) to obtain a polyvinyl alcohol solution, which was cooled to 20° C.; then 0.07 parts by weight of sodium dioctyl sulfosuccinate, 7 parts by weight of hydrochloric acid and 31.5 parts by weight of n-butyraldehyde were added to the polyvinyl alcohol solution, and then the mixture was stirred for 2 hours. The method comprises the following steps: reacting the mixture at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 11.5 wt% is obtained; washing the polyvinyl butyral suspension with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1 wt%; raising the pH value of the mixture to 11 with a sodium hydroxide solution to stabilize the mixture; subsequently, removing water with a centrifugal dryer, and air drying the mixture in an air flow drying device to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 11.5 wt%;
[0126] (4) using 3GO plasticizer and DOA plasticizer containing Tinuvin@P, Tinuvin@571 and octylphenol antioxidant (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, the amount of octylphenol antioxidant is 8g, and the amount ratio of 3GO plasticizer to DOA plasticizer is 50:50) as the second auxiliary agent, and mixing the pellets obtained in step (3) and the second auxiliary agent in a twin-screw extruder to obtain a second material; wherein the feed weight rate ratio of the plasticizer to the pellets is 45:55, and the melting temperature measured by sampling at the end of the extruder is between 170-185°C;
[0127] (5) The first material and the second material are passed through an ABA distributor, wherein A is the first material, B is the second material, and the thickness ratio of A to B is 3.4:1, to obtain a membrane material; the ABA distributor used is Figure 1 The mold shown.
[0128] Example 3
[0129] (1) polyvinyl alcohol having a degree of polymerization of 300 and polyvinyl alcohol having a degree of polymerization of 1800 are mixed in a weight ratio of 6:94 to obtain a polyvinyl alcohol mixture having an average degree of polymerization of 1700; 35 parts by weight of the polyvinyl alcohol mixture are dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water is 1:9) to obtain a polyvinyl alcohol solution, which is then cooled to 20° C.; then 0.17 parts by weight of sodium dioctyl sulfosuccinate, 3.5 parts by weight of hydrochloric acid and 17.5 parts by weight of n-butyraldehyde are added to the polyvinyl alcohol solution; The method comprises the following steps: reacting the mixture at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 18.5 wt% is obtained; washing the polyvinyl butyral suspension with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1 wt%; raising the pH value of the mixture to 11 with a sodium hydroxide solution to stabilize the mixture; subsequently, removing water with a centrifugal dryer, and air drying the mixture in an air flow drying device to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 18.5 wt%;
[0130] (2) A 3GO plasticizer containing Tinuvin@P, Tinuvin@571 and an octylphenol antioxidant (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, and the amount of octylphenol antioxidant is 8g) is used as a first auxiliary agent, and the pellets obtained in step (1) and the first auxiliary agent are mixed in a twin-screw extruder to obtain a first material; wherein the feed weight rate ratio of the first auxiliary agent to the pellets is 28:72, and an aqueous solution with a molar ratio of potassium acetate to magnesium acetate of 3:1 is injected during extrusion (the amount of the aqueous solution is 0.04% by weight of the plasticizer), and the melting temperature measured by sampling at the end of the extruder is between 170°C and 185°C;
[0131] (3) polyvinyl alcohol with a degree of polymerization of 1000 and polyvinyl alcohol with a degree of polymerization of 2700 are mixed in a weight ratio of 10:90 to obtain a polyvinyl alcohol mixture with an average degree of polymerization of 2500, 35 parts by weight of the polyvinyl alcohol mixture are dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water is 1:9) to obtain a polyvinyl alcohol solution, which is cooled to 20° C.; then 0.17 parts by weight of sodium dioctyl sulfosuccinate, 3.5 parts by weight of hydrochloric acid and 38.5 parts by weight of n-butyraldehyde are added to the polyvinyl alcohol solution. , reacting at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 9.0 wt% is obtained; washing the polyvinyl butyral suspension with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1 wt%; raising the pH value of the mixture to 11 with a sodium hydroxide solution to stabilize it; subsequently, removing water with a centrifugal dryer, and air drying it in an airflow drying device to make its water content ≤1 wt%, to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 9.0 wt%;
[0132] (4) Mixing 3GO plasticizer and DOA plasticizer containing Tinuvin@P, Tinuvin@571 and octylphenol antioxidant in a twin-screw extruder (based on 1L of 3GO plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, the amount of octylphenol antioxidant is 8g, and the amount ratio of 3GO plasticizer to DOA plasticizer is 50:50) as the second auxiliary agent, and mixing the pellets obtained in step (3) and the second auxiliary agent in a twin-screw extruder to obtain a second material; wherein the feed weight rate ratio of the second auxiliary agent to the pellets is 45:55, and the melting temperature measured by sampling at the end of the extruder is between 170-185°C;
[0133] (5) passing the first material and the second material through an ABA distributor, wherein A is the first material, B is the second material, and the thickness ratio of A to B is 3.4:1, to obtain a membrane material; the ABA distributor adopts Figure 1 The mold shown.
[0134] Example 4
[0135] The membrane material was prepared according to the method of Example 1, except that the polyvinyl alcohol mixture with an average degree of polymerization of 1700 in step (1) was replaced by polyvinyl alcohol with a degree of polymerization of 1700.
[0136] Example 5
[0137] The membrane material was prepared according to the method of Example 1, except that in step (3), the polyvinyl alcohol mixture with an average degree of polymerization of 2500 was replaced by polyvinyl alcohol with a degree of polymerization of 2500.
[0138] Example 6
[0139] The membrane material was prepared according to the method of Example 1, except that step (1) was replaced by:
[0140] (1) polyvinyl alcohol with a degree of polymerization of 300 and polyvinyl alcohol with a degree of polymerization of 1800 are mixed in a weight ratio of 6:94 to obtain a polyvinyl alcohol mixture with an average degree of polymerization of 1700, 35 parts by weight of the polyvinyl alcohol mixture are dissolved in water at 98-100° C. (the weight ratio of the polyvinyl alcohol mixture to water is 1:9) to obtain a polyvinyl alcohol solution, which is then cooled to 20° C.; then 0.14 parts by weight of sodium dioctyl sulfosuccinate, 5 parts by weight of hydrochloric acid (concentration 30-35wt%) and 20.5 parts by weight of ethanol are added to the polyvinyl alcohol solution. n-butyraldehyde is reacted at 65-70° C. until a polyvinyl butyral suspension having a hydroxyl content of 15.0wt% is obtained; the polyvinyl butyral suspension is washed with deionized water for 20 minutes each time until the residual butyraldehyde content is ≤1wt%; the pH value of the mixture is increased to 11 with a sodium hydroxide solution to stabilize it; subsequently, a centrifugal dryer is used to remove water, and the mixture is air-dried in an airflow drying device to have a moisture content of ≤1wt%, to obtain a granular white ordinary PVB resin having a residual hydroxyl value of 15.0wt%.
[0141] Example 7
[0142] The membrane material was prepared according to the method of Example 1, except that step (2) was replaced by:
[0143] (2) The pellets obtained in step (1) are mixed with a DOA plasticizer containing Tinuvin@P, Tinuvin@571 and an octylphenol antioxidant in a twin-screw extruder (based on 1L of DOA plasticizer, the amount of Tinuvin@P is 4g, the amount of Tinuvin@571 is 1.2g, and the amount of octylphenol antioxidant is 8g) to obtain a first PVB resin material; wherein the feed weight rate ratio of the plasticizer to the pellets is 28:72, and an aqueous solution with a molar ratio of potassium acetate to magnesium acetate of 3:1 is injected during extrusion (the amount of the aqueous solution is 0.02 weight % of the plasticizer).
[0144] Example 8
[0145] The membrane material was prepared according to the method of Example 1, except that in step (4), the DOA plasticizer was replaced by dioctyl phthalate (purchased from Shanghai Kunrui Chemical Co., Ltd., product model DOP).
[0146] Comparative Example 1
[0147] The membrane material was prepared according to the method of Example 1, except that the feed weight rate ratio of the second auxiliary agent to the granular material in step (4) was replaced with 55:45.
[0148] Comparative Example 2
[0149] The membrane material was prepared according to the method of Example 1, except that the ratio of the amount of 3GO plasticizer to the amount of DOA plasticizer in step (4) was 30:70.
[0150] Comparative Example 3
[0151] The membrane material was prepared according to the method of Example 1, except that the ratio of the amount of 3GO plasticizer to the amount of DOA plasticizer in step (4) was 20:80.
[0152] Comparative Example 4
[0153] The membrane material was prepared according to the method of Example 1, except that the 3GO plasticizer in step (4) was replaced by dioctyl azelate; and the feed weight rate ratio of the second auxiliary agent to the pellets was replaced by 42:58.
[0154] Comparative Example 5
[0155] The diaphragm material was prepared according to the method of Example 1, except that the 3GO plasticizer in step (2) and step (4) was replaced by dioctyl azelaic acid; the feed weight rate ratio of the first auxiliary agent to the pellets was replaced to 25:75, and the feed weight rate ratio of the second auxiliary agent to the pellets was replaced to 40:60.
[0156] Test Example 1
[0157] The refractive index, melt index and dynamic viscosity of the first material and the second material prepared in Example 1 to Example 8 and Comparative Example 1 to Comparative Example 5 were tested, and the difference in refractive index, melt index and dynamic viscosity between the first material and the second material was calculated. The results are shown in Table 1.
[0158] Table 1
[0159]
[0160]
[0161] It can be seen from the results in Table 1 that, compared with Comparative Examples 1 to 5, in the diaphragm materials obtained by the preparation method provided by the present invention in Examples 1 to 8, there is a specific refractive index difference, melt index difference and viscosity difference between the first material layer and the second material layer. The synergistic effect formed by the superposition of the first material layer and the second material layer allows the diaphragm material to have better sound insulation performance while improving its weather resistance and adhesion to the laminated glass, thereby improving the optical ghosting problem caused by the superposition of the first material layer and the second material layer, thereby improving its optical performance, while reducing the production cost, and having significant economic benefits.
[0162] Test Example 2
[0163] The molecular weight distribution of polyvinyl alcohol with a degree of polymerization of 300, 500, 1700, 1800, 1000, 2500 and 2700 was tested respectively, and the results are shown in Table 2.
[0164] The molecular weight distribution of polyvinyl alcohol with an average degree of polymerization of 1700 obtained by mixing polyvinyl alcohols with degrees of polymerization of 300 and 1800 at a weight ratio of 6:94 was tested, and the results are shown in Table 2;
[0165] The molecular weight distribution of polyvinyl alcohol with an average degree of polymerization of 1700 obtained by mixing polyvinyl alcohols with degrees of polymerization of 500 and 1800 at a weight ratio of 8:92 was tested, and the results are shown in Table 2;
[0166] The molecular weight distribution of polyvinyl alcohol with an average degree of polymerization of 2500 obtained by mixing polyvinyl alcohols with degrees of polymerization of 1000 and 2700 in a weight ratio of 10:90 was tested. The results are shown in Table 2.
[0167] Table 2
[0168]
[0169]
[0170] It can be seen from the results in Table 2 that, compared with polyvinyl alcohol with a degree of polymerization of 1700 and 2500 (Example 4 and Example 5), the mixed polyvinyl alcohol with an average degree of polymerization of 1700 and 2500 (Example 1-Example 3 and Example 6-Example 8) has a higher proportion of small molecular weight, which increases the gap between molecules while increasing the molecular contact area, which is beneficial to the discharge of air when the glass is combined, thereby increasing the adhesion between the film and the glass; moreover, the proportion of small molecules fills the gap between the PVB resin molecules produced using a single polyvinyl alcohol as a raw material, and increases the contact area between the molecules, thereby improving the performance of the PVB film and increasing the ability to adapt to environmental changes, that is, improving the weather resistance of the product.
[0171] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A diaphragm material, characterized in that: The membrane material includes at least one first material layer and at least one second material layer; The difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melt index between the first material layer and the second material layer is not higher than 0.5 g / 10 min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400 Pa·s.
2. The diaphragm material according to claim 1, characterized in that: The refractive index of the first material layer is 1.47-1.49, the melt index is 1.05-1.24 at a load of 21.6 kg and a temperature of 120° C., and the dynamic viscosity is 1960-2180 Pa·s at a temperature of 180° C.
3. The diaphragm material according to claim 1 or 2, characterized in that: The first material layer contains a first PVB resin and a first auxiliary agent, the second material layer contains a second PVB resin and a second auxiliary agent, the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, the second auxiliary agent contains a first plasticizer and a second plasticizer, and the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01; Preferably, the first plasticizer is selected from at least one of triethylene glycol diisooctanoate, dioctyl azelate and dioctyl sebacate, and more preferably triethylene glycol diisooctanoate; Preferably, the second plasticizer is at least one selected from dihexyl adipate, dioctyl phthalate, dioctyl terephthalate, dinonyl terephthalate and dioctyl adipate, and more preferably dioctyl adipate.
4. The diaphragm material according to claim 3, characterized in that: The content of the first auxiliary agent in the first material layer is 26.0-28.5wt%; Preferably, the hydroxyl value of the first PVB resin is 17-19 wt %; Preferably, in the second material layer, the content of the second auxiliary agent is 42-46wt%; Preferably, in the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2; Preferably, the hydroxyl value of the second PVB resin is 9-13 wt %.
5. The diaphragm material according to claim 1 or 2, characterized in that: The membrane material comprises two layers of the first material layer and one layer of the second material layer, and the two layers of the first material layer are arranged on both sides of the second material layer; Preferably, the thickness of the first material layer is 280-320 μm, and the thickness of the second material layer is 80-120 μm; Preferably, at least one side of the first material layer along the length direction is in a wedge-shaped structure from the middle to the end; Preferably, the ratio of the maximum thickness of the first material layer to the thickness of the second material layer is 3.4-3.6:
1.
6. A method for preparing a diaphragm material, characterized in that: The following steps are involved: Extruding and pressing a first material to form a first material layer, extruding and pressing a second material to form a second material layer, and pressing at least one layer of the first material layer and at least one layer of the second material layer; Among them, the difference in refractive index between the first material layer and the second material layer is not higher than 0.01; under the conditions of a load of 21.6 kg and a temperature of 120°C, the difference in melt index between the first material layer and the second material layer is not higher than 0.5 g / 10 min; under the condition of a temperature of 180°C, the difference in dynamic viscosity between the first material layer and the second material layer is not higher than 400 Pa·s.
7. The preparation method according to claim 6, characterized in that: The preparation process of the first material includes: S1, mixing a first polyvinyl alcohol, a surfactant I, a catalyst I and butyraldehyde and performing a heating reaction I to obtain a first PVB resin; S2, mixing the first PVB resin and the first auxiliary agent, and then plasticizing and extruding; the first auxiliary agent contains a first plasticizer with a refractive index of 1.44-1.46, and the weight ratio of the first auxiliary agent to the first PVB resin is 0.35-0.40:1; Preferably, the preparation process of the second material includes: (a) mixing a second polyvinyl alcohol, a surfactant II, a catalyst II and butyraldehyde and heating them for reaction II to obtain a second PVB resin; (b) mixing the second PVB resin and the second auxiliary agent and then plasticizing and extruding; the second auxiliary agent contains a first plasticizer and a second plasticizer, the difference in refractive index between the first plasticizer and the second plasticizer is less than 0.01, and in the second auxiliary agent, the weight ratio of the first plasticizer to the second plasticizer is 1:0.8-1.2, and the weight ratio of the second auxiliary agent to the second PVB resin is 0.72-0.86:
1.
8. The preparation method according to claim 7, characterized in that: The first plasticizer is selected from at least one of triethylene glycol diisooctanoate, dioctyl azelate and dioctyl sebacate, and is more preferably triethylene glycol diisooctanoate; Preferably, the second plasticizer is at least one selected from dihexyl adipate, dioctyl phthalate, dioctyl terephthalate, dinonyl terephthalate and dioctyl adipate, and more preferably dioctyl adipate; Preferably, the hydroxyl value of the first PVB resin is 17-19 wt %; Preferably, the hydroxyl value of the second PVB resin is 9-13 wt %.
9. The preparation method according to claim 7 or 8, characterized in that: The average polymerization degree of the first polyvinyl alcohol is 1600-1800; Preferably, the first polyvinyl alcohol comprises polyvinyl alcohol I and polyvinyl alcohol II, the degree of polymerization of the polyvinyl alcohol I is 300-500, and the degree of polymerization of the polyvinyl alcohol II is 1800-2000; Preferably, the average degree of polymerization of the second polyvinyl alcohol is 2400-2600; Preferably, the second polyvinyl alcohol comprises polyvinyl alcohol III and polyvinyl alcohol IV, the degree of polymerization of the polyvinyl alcohol III is 1000-1500, and the degree of polymerization of the polyvinyl alcohol IV is 2600-2700; Preferably, the surfactant I and the surfactant II are each independently selected from at least one of dioctyl sodium sulfosuccinate, dodecylbenzenesulfonic acid, sodium dodecyl sulfonate and sodium dodecyl sulfate; Preferably, the catalyst I and the catalyst II are each independently selected from at least one of hydrochloric acid, sulfuric acid and maleic acid.
10. Use of the membrane material according to any one of claims 1 to 5 and / or the membrane material obtained by the preparation method according to any one of claims 6 to 9 in laminated glass.
11. A laminated glass, characterized in that: The invention comprises the membrane material according to any one of claims 1 to 5 and / or the membrane material obtained by the preparation method according to any one of claims 6 to 9 and two glass layers, wherein the membrane material is located between the two glass layers.